The Evolution of Media Communication - Peña Acuña, Beatriz (IntechOpen, 2017)
Media communication is a young discipline, if we compare it with others. It has been studied scientifically from the last century in social sciences. This topic, as it is a human process, is complex, and it is changing because of new technologies. It transforms our society too. It is recognised that we are in a communication society. The management of knowledge is settled in business area too. Communication skills are recognised as competences in education for preparing future citizens. Media communication feeds from different disciplines and it keeps their attention. This book is an attempt to provide theoretical and empirical framework to better understand media communication from different point of views and channels in various contexts. The international authors are specialised on the issues. They cover a wide range of updated issues. They span from deepening about behaviour of media or trends to national cases related to social net and to new phenomena - as it is mindfulness applied to creativity. So in this book, two sections are presented. The first section focuses on the behaviour of media, when it is applied in education field and reception research. The second section provides three case studies about the Internet: platforms and social nets developed and applied to different publics.